Interactive effects of temperature, cadmium, and hypoxia on rainbow trout (Oncorhynchus mykiss) liver mitochondrial bioenergetics - John O. Onukwufor; Collins Kamunde (Ecotoxicology and Environmental Safety)
Fish in their natural environments possess elaborate mechanisms that regulate physiological function to mitigate the adverse effects of multiple environmental stressors such as temperature, metals, and hypoxia. We investigated how warm acclimation affects mitochondrial responses to Cd, hypoxia, and acute temperature shifts (heat shock and cold snap) in rainbow trout. We observed that state 3 respiration driven by complex I (CI) was resistant to the stressors while warm acclimation and Cd reduced complex I +II (CI + II) driven state 3 respiration. In contrast, state 4 (leak) respirations for both CI and CI + II were consistently stimulated by warm acclimation resulting in reduced mitochondrial coupling efficiency (respiratory control ratio [RCR]). Warm acclimation and Cd exacerbated their individual effect on leak respiration to further reduce the RCR. Moreover, the effect of warm acclimation on mitochondrial bioenergetics aligned with its inhibitory effect on activities of citrate synthase and both CI and CII. Unlike the Cd and warm acclimation combined exposure, hypoxia alone and in combination with warm acclimation and/or Cd abolished the stimulation of CI and CI + II powered leak respirations resulting in partial recovery of RCR. The response to acute temperature shifts indicated that while state 3 respiration returned to pre-acclimation level, the leak respiration did not. Overall, our findings suggest a complex in vivo interaction of multiple stressors on mitochondrial function that are not adequately predicted by their individual effects.